On the conditional effects of IMF program participation on output growth - Michael Binder; Marcel Bluhm (Center for Economic Studies and ifo Institute (CESifo), 2010)
The empirical evidence currently available in the literature regarding the effects of a country's IMF program participation on its output growth is rather mixed. To shed new evidence on this issue, in this paper we specify a state-dependent panel data model accounting in particular for program participation selection and the potential conditionality of the output growth effects of program participation on a country's degree of program implementation and institutional factors such as quality of governance, internal stability, health, and educational attainment. We find that the effects of IMF program participation on output growth vary systematically with the degree of program implementation as well as our index of institutional factors, and that these effects are positive only if the IMF program is implemented to a sufficient degree or if the program participation is coupled with sufficient progress in improving institutional quality.
Keywords: O11; O19; C33; 330; IMF program participation; output growth; panel sample selection models; conditional pooling; Anpassungsprogramm des IWF; Wirkungsanalyse; Wirtschaftswachstum; Panel; Schätzung; Welt